Game Development of “Prokes” to Socialize the Prevention of Covid-19 - Cahya Dewi, Dewa Ayu Indah; Yasa, Ngakan Putu Darma (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
The level of awareness of the Indonesian people to orderly and comply with the implementation of health protocols is still very low. Special touch to young people is needed in socializing health protocols and new normal life. Game of “Prokes” is expected as a means for socialization of covid-19 prevention. The proposed method is agile method that is combined using shuffle random algorithm to randomize question in quiz of this game. The blackbox result was 100% functionality of the game has run well.  There was a significant difference between user knowledge before and after playing the game of “Prokes” as indicated by t value of 2.297, t table value of 2.004, and the critical value of ? = 0.05. The proposed method had an GEQ result of 3.04. Therefore, the game feasible as a means of socialization in prevention covid-19 using health protocols and new normal for the young generations.